2018
DOI: 10.3389/fphys.2018.00052
|View full text |Cite
|
Sign up to set email alerts
|

Niemann-Pick C2 Proteins: A New Function for an Old Family

Abstract: Niemann-Pick proteins type C2 (NPC2) are carriers of cholesterol in vertebrates, with a single member in each species. The high sequence conservation between mammals and across vertebrates is related to their common function. In contrast, NPC2 proteins in arthropods have undergone extensive duplication and differentiation, probably under environmental pressure, and are likely to have different functions. Recent studies have suggested that in arthropods these proteins might act as carriers for semiochemicals an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 47 publications
3
50
0
Order By: Relevance
“…This study found that NPC2 was expressed not only in chemosensory sensilla, but also in other parts of the body, suggesting roles in both chemical detection as well as in other functions. The results of this study were consistent with other studies in arthropods, which showed wide expression of NPC2 proteins across the body (Ishida et al, 2014; Pelosi et al, 2017; Zhu et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…This study found that NPC2 was expressed not only in chemosensory sensilla, but also in other parts of the body, suggesting roles in both chemical detection as well as in other functions. The results of this study were consistent with other studies in arthropods, which showed wide expression of NPC2 proteins across the body (Ishida et al, 2014; Pelosi et al, 2017; Zhu et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…XP_001844693), indicating a result of contamination. Furthermore, the two CSPs reported in a transcriptome study of the mite Tyrophagus putrescentiae 29 A third family of proteins possibly acting as semiochemical carriers in insects include the NPC2 (Niemann-Pick proteins of type C2) proteins [30][31][32] . This family is well represented in Chelicerata with a variable number of genes 31,33 , depending on the species.…”
Section: Communication Betweenmentioning
confidence: 99%
“…Members of the NPC2 family have been also found in the tick Amblyomma americanum 35 and eight transcripts encoding such proteins have recently been reported in a transcriptome project in Varroa chemosensory organs 26 . For NPC2 proteins, a function of semiochemical carriers seems to be well supported by their ligand-binding properties as well as by their localization in chemosensilla 30,32,34 . Moreover, three-dimensional structures of NPC2 members both from vertebrates and insects are available, some of them containing hydrophobic ligands inside their binding pockets 30,36 .…”
Section: Communication Betweenmentioning
confidence: 99%
“…The role of NPC2s as semiochemical carriers, and not just as lipid carriers, is a relatively new concept that emerged from the discovery of CjapNPC2, which binds to several semiochemicals in the basiconica sensilla on the antennae of the ant Camponotus japonicus (Ishida et al, 2014). This discovery led to the finding of NPC2 homologues in other arthropods, but only a few NPC2s were suggested to play a role as semiochemicals carriers, also in insects (Zhu et al, 2018). We searched the Varroa transcriptome for possible CjapNPC2 homologues using a local BLASTp search (accession ID: BAO48214) and found that TRINITY_DN80297_c0_g1_i1, one of the six Varroa NPC2 members, had the highest similarity across the entire Varroa transcriptome (e-value = 3 E-17), suggesting that this transcript is a Varroa CjapNPC2 homologue.…”
Section: Two Families Of Soluble Carrier Proteins: Npc2 and Obpsmentioning
confidence: 99%